A New Way to Assess Brand Equity of Automotive Brands - Kantar, Murat; Bardakci, Ahmet (European Scientific Journal, ESJ, 2017)
The concept of brand equity is so appealing nevertheless measuring of it is not as easy as its appeals. Aaker (1996) proposes some ways including price premium for assessing the brand equity. Used car markets may be one of the most appropriate markets to observe price premiums mainly due to the actual conditions of cars may not be examined but brands become the primary determinants of prices of used cars. The main assumption is that if the brand has own an equity, depreciating value of to be used would be less than that of the brand which has a relatively lesser equity. This study aims to assess brand equity in used car market in Turkey by analyzing depreciation differences among specific brands. Findings of the study supports the idea that observing depreciation differences among brands is a useful approach to assess brand equities.